(untitled) (Journal of Health Sciences, 2016)
Introduction: Our aim was to evaluate quality of life (QOL) as a predictor of work abilities of employees in a tobacco factory.Methods: The study was performed in the period between 2011 and 2012. The sample comprised of 270 workers, males and females, aged from 20-65, with different educational backgrounds. The study was performed as cross-sectional research, on a voluntary basis, using two standardized and anonymous questionnaires: The World Health Organization Quality of Life-Brief Version questionnaire (WHOQOL-BREF) and the Work Ability Index questionnaire (WAI).Results: The participants subjectively perceived high values of QOL in general, with the highest values in the area of living environment. The lowest value was in the area of social interactions. Statistically significant differences were observed in the subjective assessments of QOL, especially in three defined areas (physical health, mental health, and social interactions). Workers age 50-65 years and workers with basic (primary) level of education exhibited a suboptimal (<70%) values in total value and the values of individually defined areas of QOL.Conclusions: Strong predictors of exemplary work ability of employees are good physical and mental health, younger age, and higher level of education. A link was observed between suboptimal work ability and dissatisfaction with profession and working environment, frequent illness, absenteeism, and exposure to health risks at the workplace.